THE DEVELOPMENT OF BLENDED LEARNING KIT USING SOCIAL MEDIA EDMODO ON GLOBAL WARMING TOPIC - HAYYU DIAN RAMADHANI, PUTRI (Inovasi Pendidikan Fisika, 2017)
In general, blended learning is an educational program that combines several technologies (such as internet and smartphone), and learning methods/models (face-to-face and virtual) in one teaching/learning process. Therefore, blended learning is categorized as an innovative learning process and it is believed can develop student’s skills in critical thinking, processing information, and in information and communication technology (ICT). The research carried in this “skripsi” document applied blended learning by combining face-to-face learning in class and virtual learning using Edmodo that can be accessed by the teacher and the students via their smartphones. The Global Warming topic was chosen as the learning material in this work. Edmodo is a web-based social learning network that intentionally designed for teachers and students to interact in a virtual learning process. The ADDIE model was adapted to develop the learning kit. In this kit, the aspect of validity, practicability, and effectiveness were described. The kit was tested via one-shot case study to the twenty-five numbers of students in the Science-5 class, SMA Negeri 6 Surabaya. The result revealed that: (1) the overall learning kit are very valid; (2) the aspect of practicability is excellent; and (3) the aspect of the effectiveness are excellent because 92,00 % of the students have passed the minimum standard score and 81,34 % of them gave positive response to the learning process. Keywords: learning kit, blended learning, Edmodo